The Post- Covid-19 Pandemic Learning Loss in 3T Regions, What Can We Try? - Syabily, Aulia Aniz; Sari, Ikke Pradima; Ilmi, Sholikhatul (Universitas Nusa Cendana, 2024)
The Covid-19 pandemic has necessitated a shift from face-to-face learning to online learning. This transition has led to an alarming phenomenon known as learning loss, characterised by a decline in students' academic knowledge and skills. The impact of the Covid-19 pandemic makes vulnerable to setbacks one of which is students in Disadvantaged, Frontier, and Outermost (3T) areas where inadequate infrastructure, such as limited internet access, and lack of technological proficiency hinder effective learning. The context of this article is in the 3T areas, especially Merauke. Addressing learning loss is crucial to prevent long-term consequences such as exacerbating educational disparities and reducing the overall quality of human capital. Meanwhile, there is a research gap investigating the impact of learning loss and proposing effective strategies to overcome this problem. This article uses descriptive analysis. This article comprehensively explores the impact of learning loss in 3T areas and presents effective mitigation approaches to address this challenge.